Migration and distribution of the veined squid, Loligo forbesi, in Scottish (UK) waters - Viana, Mafalda (2011)
Dissertação de mest., Biologia Marinha, 2007, Universidade do Algarve, Faculdade de Ciências do Mar e do Ambiente